The Relationship between nutritional status and menstrual cycle and anemia - Lumastari Ajeng Wijayanti; Satria Eureka Nurseskasatmata (Jurnal Ilmiah Kesehatan Sandi Husada)
Introduction: Adolescence is a period of growth and puberty; adolescents are very concerned about appearance, so they pay attention to their diet until they are strict. This causes the intake needed to be unmet, then impacts the menstrual cycle and anemia.